PENGARUH KOMPETENSI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TELKOM INDONESIA WILAYAH SULAWESI SELATAN (Studi kasus pada PT. Telkom Makassar STO Balaikota) - Kusnadi Arifin (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this study was to analyze the influence of competence, work motivation and work environment on employee performance at PT Telkom Makassar STO Balaikota office. The number of population in this study is all employees of PT Telkom Makassar STO City Hall of 117 people. With a relatively large number of population (117 people), then the sampling using slovin formula so that 90 respondents obtained. This research was conducted by using survey approach, the type of research conducted is descriptive quantitative. The data were collected by using questionnaires, literature and observation. Data analysis used descriptive and Inferential statistics (multiple linear regression). The results of this study indicate that partially or simultaneously competence variables, work motivation and work environment affect positively and significantly the performance of employees at the office of PT Telkom Makassar STO City Hall. While work motivation variable is the most dominant variable affecting employee performance at PT Telkom Makassar STO Balaikota.